An analysis of teachers’ classroom interaction by using self-evaluation of teacher talk - Riski Valentika; Yuyun Yulia (Journal of English Language and Pedagogy, 2020)
This study focuses on classroom interaction in English teaching and learning at SMA Muhammadiyah 1 Bengkulu. The objective of this study is to 1. Describe student-teacher interaction pattern, 2. Find out the type of interactional features in the classroom. The data were first-grade students. This study shows how teacher and student talk and give a response to each other. This study is conducted in form of discourse analysis. The writer used observation to get the data. The data were in a form video recording of classroom interactional both teachers and students. The writer made transcription from recorded data and analyzed it through IRF exchange structure and applied Walsh’s framework in interactional features. The result of the research showed teacher A and B interaction pattern is Initiation (I)- Response (R)- Feedback (F). Teacher A’s pattern was I (initiation), R (response) and F (feedback). In her classrooms, teacher A provides lots of initiation to her students.  Teacher B’s pattern was IRF in this class with the highest amount of initiation in form question. Teacher A used 12 (twelve) interactional feature based on Walsh framework (2006). There were extended learner turn (ELT) 171 frequencies, extended teacher turn (ETT) 90 frequencies,  Display Question (DQ) 66 frequencies, confirmation check (CC) 36 frequencies, seeking clarification (SC) 35 frequencies, Teacher echo (TE) 27 frequencies, referential question (RQ) 20 frequencies, Scaffolding (SCF) 16 frequencies, extended wait time (EWT) 13 frequencies, turn completion (TC) 12 frequencies, direct repair (DR) 5 frequencies, content feedback (CF) 1 frequency. Teacher B used 12 (twelve) interactional feature based on Walsh framework (2006). There were extended learner turn (ELT) 155 frequencies, Display Question (DQ) 53 frequencies, extended teacher turn (ETT) 42 frequencies, referential question (RQ) 23 frequencies, confirmation check (CC) 17 frequencies, seeking clarification (SC) 13 frequencies, Form focus feedback (FFF) 12, Teacher echo (TE) 8 frequencies, Scaffolding (SCF) 8 frequencies, extended wait time (EWT) 7 frequencies, turn completion (TC) 4 frequencies, direct repair (DR) 3 frequencies. Both of teacher  A and B provide a lot of extended learner turn by giving a direct question and referential question. Students’ response frequently in English, in Indonesian and in another hand in their mother tongue.